1996
DOI: 10.1111/j.1432-1033.1996.0728w.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteases from Trypanosoma brucei brucei

Abstract: African trypanosomes contain proteases that may be released into the bloodstream of their infected hosts. This paper describes a novel, combined isolation of a cysteine proteinase (called trypanopain-Tb) and a serine oligopeptidase (which we call oligopeptidase-Tb) from Trypanosoma brucei brucei, as well as a comparison of the activities of these two enzymes against several host regulatory molecules.The enzymes differed in various respects. Firstly, purified trypanopain-Tb was shown to readily cleave proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 42 publications
1
68
0
Order By: Relevance
“…However, OP-Tb activity is enhanced in the presence of reducing agents and polyamines [8]. Since melarsoprol therapy depletes intracellular reducing agents (namely trypanothione) and since DFMO therapy depletes intracellular polyamine levels [28] either drug may down-regulate OP-Tb activity within trypanosomes through the depletion of intracellular OP-Tb activators.…”
Section: Resultsmentioning
confidence: 99%
“…However, OP-Tb activity is enhanced in the presence of reducing agents and polyamines [8]. Since melarsoprol therapy depletes intracellular reducing agents (namely trypanothione) and since DFMO therapy depletes intracellular polyamine levels [28] either drug may down-regulate OP-Tb activity within trypanosomes through the depletion of intracellular OP-Tb activators.…”
Section: Resultsmentioning
confidence: 99%
“…congolense possesses at least two families of CPs, named CP1 and CP2, the latter also known as congopain or trypanopain-Tc [207], while the enzymes in T. b. brucei and T. b. rhodesiense are termed trypanopain-Tb (or brucipain) and rhodesain, respectively [204,205].…”
Section: Peptidases In African Trypanosomes Cysteine Peptidasesmentioning
confidence: 99%
“…These enzymes share structural and functional similarities with T. cruzi cruzipain [203][204][205][206].…”
Section: Peptidases In African Trypanosomes Cysteine Peptidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that OP-Tb isolated directly from trypanosomes was not inhibited by mammalian plasma serpins (17). OP-Tb activity is therefore unregulated after release into the bloodstream.…”
mentioning
confidence: 99%